Fragile X mental retardation protein expression in Alzheimer’s disease - Renoux, Abigail J.; Carducci, Nicholas M.; Ahmady, Arya A.; Todd, Peter K. (Frontiers in Genetics, 2014)
The FMR1 protein product, FMRP, is an mRNA binding protein associated with translational inhibition of target transcripts. One FMRP target is the amyloid precursor protein (APP) mRNA, and APP levels are elevated in Fmr1 KO mice. Given that elevated APP protein expression can elicit Alzheimer’s disease (AD) in patients and model systems, we evaluated whether FMRP expression might be altered in Alzheimer’s autopsy brain samples and mouse models compared to controls. In a double transgenic mouse model of AD (APP/PS1), we found no difference in FMRP expression in aged AD model mice compared to littermate controls. FMRP expression was also similar in AD and control patient frontal cortex and cerebellum samples. Fragile X-associated tremor/ataxia syndrome (FXTAS) is an age related neurodegenerative disorder caused by expanded CGG repeats in the 5’UTR of the FMR1 gene. Patients experience cognitive impairment and dementia in addition to motor symptoms. In parallel studies, we measured FMRP expression in cortex and cerebellum from three FXTAS patients and found reduced expression compared to both controls and Alzheimer’s patient brains, consistent with animal models. We also find increased APP levels in cerebellar, but not cortical, samples of FXTAS patients compared to controls. Taken together, these data suggest that a decrease in FMRP expression is unlikely to be a primary contributor to Alzheimer’s disease pathogenesis.